An ultra-sensitive and ratiometric fluorescent probe based on the DTBET process for Hg2+ detection and imaging applications. Issue 4 (19th December 2018) - Jiang, Yin; Duan, Qinya; Zheng, Guansheng; Yang, Liu; Zhang, Jie; Wang, Yafeng; Zhang, Huatang; He, Jun; Sun, Hongyan; Ho, Derek
Abstract : A ratiometric fluorescent probe based on DTBET has been designed, which shows >30 000-fold fluorescence ratio increment upon reaction with Hg 2+ . Abstract : In this article, we present an ultra-sensitive and ratiometric fluorescent probe (TR-Hg ) for Hg 2+ detection based on the mechanism of aggregation induced emission (AIE) and dark through-bond energy transfer (DTBET). The probe was constructed using tetraphenylethene as the dark donor and rhodamine B thiolactone as the acceptor. By exploiting the advantages of DTBET, which eliminates emission leakage from dark donors and provides nearly 100% energy transfer efficiency, TR-Hg exhibits more than a 30 000-fold fluorescence ratio enhancement after reacting with Hg 2+ .TR-Hg demostrates (i) a detection limit of 43 pM, which is the lowest among the reported ratiometric Hg 2+ probes, (ii) excellent selectivity, fast response-time (<10 s) and a wide pH application range, (iii) strong applicability for paper-based colorimetric assay, where readout can be performed by the naked eye, and (iv) fluorescent imaging of Hg 2+ in onion epidermal tissues, indicating its potential use in living organisms.